Adoption of multiple sustainable land management practices among irrigator rural farm households of Ethiopia - Bekele, Rahel Deribe; Mirzabaev, Alisher; Mekonnen, Dawit Kelemework (John Wiley & Sons, 2021)
Using a household and plot-level survey conducted in Ethiopia, this study analyzes the difference in farmers’ adoption of sustainable land management (SLM) practices between their rainfed and irrigated plots. The paper also investigates the varying influence of different types of irrigation water management systems and associated irrigation technologies on the adoption of SLM practices in irrigated plots. After controlling for heterogeneity among different irrigation water management systems and technologies, we found that access to irrigation play major role in enhancing farmers’ motivation to adopt more SLM practices. Furthermore, the combined effect of irrigation water management system and irrigation technology on type and number of SLM practices adopted is quite varied and very significant. The evidence highlights that farmers adopt more SLM practices in their plots with pump irrigation compared to those plots where gravity irrigation is applied because pump irrigation systems enhance complementarities with SLM practices. Finally, the findings underscore that the type of irrigation water management and the irrigation technology applied play an important role in restoring degraded lands and maintaining soil fertility, even when farmers’ adoption of irrigation was not explicitly triggered by concerns for soil health.